Emergence of undifferentiated colonies from mouse embryonic stem cells undergoing differentiation by retinoic acid treatment - Sharova, Lioudmila V. (In Vitro Cell Dev Biol Anim, 2016)
Retinoic acid (RA) is one of the most potent inducers of differentiation of mouse embryonic stem cells (ESCs). However, previous studies show that RA treatment of cells cultured in the presence of a leukemia inhibitory factor (LIF) also result in the upregulation of a gene called Zscan4, whose transient expression is a marker for undifferentiated ESCs. We explored the balance between these two seemingly antagonistic effects of RA. ESCs indeed differentiated in the presence of LIF after RA treatment, but colonies of undifferentiated ESCs eventually emerged from these differentiated cells — even in the presence of RA. These colonies, named secondary colonies, consist of three cell types: typical undifferentiated ESCs expressing pluripotency genes such as Pou5f1, Sox2, and Nanog; cells expressing Zscan4; and endodermal-like cells located at the periphery of the colony. The capacity to form secondary colonies was confirmed for all eight tested ESC lines. Cells from the secondary colonies — after transfer to the standard ESC medium — retained pluripotency, judged by their strong alkaline phosphatase (ALP) staining, typical colony morphology, gene expression profile, stable karyotype, capacity to differentiate into all three germ layers in embryoid body formation assays, and successful contribution to chimeras after injection into blastocysts. Based on flow cytometry analysis (FACS), the proportion of Zscan4-positive cells in secondary colonies was higher than in standard ESC colonies, which may explain the capacity of ESCs to resist the differentiating effects of RA and instead form secondary colonies of undifferentiated ESCs. This hypothesis is supported by cell-lineage tracing analysis, which showed that most cells in the secondary colonies were descendents of cells transiently expressing Zscan4.